Transforming Learning to Online Education 4.0 during COVID-19: Stakeholder Perception, Attitude, and Experiences in Higher Education Institutions at a Tier-III City in India. (7th April 2023) - Gupta, Ankur; Sawhney, Sahil; Nanda, Ankita; Shabaz, Mohammad; Ofori, Isaac
Abstract : Higher education institutions worldwide had to quickly pivot to delivering online classes as the COVID-19 pandemic set in. This disruption brought into focus institutional preparedness to ensure academic continuity, faculty proficiency in the use of ICT, and student readiness to adapt to an online-only model suggested in Education 4.0 framework. The Education 4.0 framework emphases to use advance technology and tools to transform education system. It was initially envisaged that the online-only model of education will at best be a stop-gap arrangement. However, as the pandemic continues unabated across India, the education community needs actionable data to fine-tune its online delivery model, to ensure its effectiveness, and retain its value perception in the eyes of the stakeholders. This is a critical aspect as evidence suggests that the initial high level of online engagement is petering out due to overexposure, mental saturation, and fatigue among both the students and faculty members. This research paper examines the perceptions, attitudes, and experiences of stakeholders involved in online education from Jammu, a Tier-III city in India. The study asserts that real "value creation" in an online mode can happen when all the stakeholders are equally motivated and working together. Institutions need to prioritize value delivery, support faculty members, provide the needed resources, and set clear expectations.